2021
DOI: 10.1051/e3sconf/202126302017
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm for selecting the structures of coastal protection construction to ensure environmentally safe condition of the coastal urbanized recreational areas

Abstract: The existing concepts and modern methods of ensuring the ecological safety of the coastal zone of the sea were analyzed. The article considers modern theoretical developments and methods of choosing design solutions for special structures – various coastal protection structures (permeable, impermeable, made of various building materials, various shapes). This paper suggests a new algorithm for the choice of Bank protection structures intending to ensure environmentally friendly seaside state urban recreation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…At the same time, the presence of calcareous monoliths in the underwater part of the sea near the village of Uglovoye was previously revealed. The formation of underwater elevations by 1-3 m leads to the transformation of the shore and waves -a change in their internal structure and external shape along the route [15] and according to the results of the survey of these sites it can be concluded that the identified process of formation of underwater elevations leads to the preservation of the beach width in this place.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…At the same time, the presence of calcareous monoliths in the underwater part of the sea near the village of Uglovoye was previously revealed. The formation of underwater elevations by 1-3 m leads to the transformation of the shore and waves -a change in their internal structure and external shape along the route [15] and according to the results of the survey of these sites it can be concluded that the identified process of formation of underwater elevations leads to the preservation of the beach width in this place.…”
Section: Resultsmentioning
confidence: 94%
“…This confirms the conclusion that the implementation of previously local coastal protection measures did not allow solving the problems in a complex. Long-term field observations [16] show that the creation of coastal protection in certain local areas gives only a temporary positive effect and can have very negative effects on neighboring areas of the beach territory, without considering the patterns of directions of long-shore sediments and wave loads. Consequently, the coastal protection issue should be resolved within the boundaries of morphological units of territories, considering the conditions of a single system.…”
Section: Discussionmentioning
confidence: 99%